Homozygous of MRP4 Gene rs1751034 C Allele Is Related to Increased Risk of Intravenous Immunoglobulin Resistance in Kawasaki Disease - Wang, Yanfei; Xu, Yufen; Huang, Ping; Che, Di; Wang, Zhouping; Huang, Xijing; Xie, Xiaofei; Li, Wei; Zhang, Li; Gu, Xiaoqiong (Frontiers in Genetics, 2021)
Background: Kawasaki disease (KD) is a systemic vasculitis in childhood, which mainly causes damage to coronary arteries, and intravenous immunoglobulin (IVIG) is the initial therapy. IVIG resistance increased risk of coronary complication in KD. And genetic background is involved in the occurrence of IVIG resistance. Our previous study indicated the susceptibility of Multi-drug resistance protein 4 (MRP4) SNPs to KD. This study was to clarify the relationship between MRP4 polymorphisms and IVIG resistance. Methods: We genotyped the six polymorphisms of MRP4 gene in 760 cases of KD using Taqman methods. Results: Among the six polymorphisms, only the rs1751034 polymorphism was significantly associated with IVIG resistance in KD [CC vs. TT: adjusted odds ratio (OR) = 2.54, 95% confidence interval (CI) = 1.21-5.34; CC vs. TT/TC: adjusted OR = 2.33, 95% CI = 1.12-4.83, P=0.023]. Combined analysis of three polymorphisms indicated that patients with 3-6 risk genotypes exhibited significantly elevated risk of IVIG resistance, when compared with those with 0–2 risk genotypes (adjusted OR= 1.52, 95% CI = 1.04-2.22, P = 0.0295). Stratified analysis revealed that in term of age and gender, rs1751034 CC carriers were associated with increased risk of IVIG resistance in those aged ≤ 60 months (adjusted OR=2.65, 95% CI=1.23-5.71, P=0.0133). The presence of three or more risk genotypes was significantly associated with risk of IVIG resistance in children younger than 5 years of age and males. Conclusion: Our results suggest that MRP4 rs1751034 CC is associated with increased risk of IVIG resistance in KD.